Cover Image, Volume 7, Issue 2. (March 2016) - Allan, Rob; Endfield, Georgina; Damodaran, Vinita; Adamson, George; Hannaford, Matthew; Carroll, Fiona; Macdonald, Neil; Groom, Nick; Jones, Julie; Williamson, Fiona; Hendy, Erica; Holper, Paul; et al.
Abstract : The cover image, by Rob Allan et al., is based on the Opinion Towards integrated historical climate research: the example of ACRE (Atmospheric Circulation Reconstructions over the Earth), DOI:10.1002/wcc.379 . Abstract : The cover image, by Rob Allan et al., is based on the Opinion Towards integrated historical climate research: the example of ACRE (Atmospheric Circulation Reconstructions over the Earth), DOI:10.1002/wcc.379 .